Effect of Presence of Ammonia in Aqueous Solution on Urea Adsorption Capacity Using Porous Carbon - Prasetyo, Imam; Rahayu, Theresia Evila Purwanti Sri; Ariyanto, Teguh (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2019)
Urea is the main source of nitrogen for plants. Conventional urea fertilizer is made by reacting ammonia and carbon dioxide. Wastewater produced by urea fertilizer plants usually contains urea and ammonia in high concentrations. In each m3 of wastewater urea content can reach 650 - 4000 ppm and ammonia amounting to 100 - 1300 ppm. The disposal of wastewater that still contains urea and ammonia with high levels can cause eutrophication in waters which is very detrimental to aquatic organisms. The uptake of urea in the urea fertilizer plant wastewater is an interesting study because it can provide a double benefit of reducing the concentration of urea in wastewater so that it can meet environmental quality standards that are environmentally friendly and obtain cheap urea fertilizer for plants. This study aims to determine the adsorption capacity of urea with porous carbon if there is ammonia in the liquid. Porous carbon is made from pyrolysis of coconut shell which is oxidized with sulfuric acid. The oxidation process is carried out by heating porous carbon which is immersed in a 50% w/w sulfuric acid solution at 90oC for 2 hours. The adsorption process is carried out at room temperature with an initial concentration of urea between 500 - 8000 ppm in a solution of urea-ammonia as a simulated liquid. The results showed that the urea adsorption capacity increased significantly in urea-ammonia solution compared to urea solution with an increase of 41%. The capacity of urea adsorption in urea-ammonia solution is 27 - 444 mg urea / g carbon.